Analysis of Ruangguru as the Online Learning Media on Chemistry Learning - Mas'udah Mas'udah; Salamah Agung; Evi Sapinatul Bahriah (Journal of Educational Chemistry (JEC), 2022)
Ruangguru is one of the leading online education platforms in Indonesia that has followed a learning system based on the applicable curriculum. There is a need for analysis to find out how capable the Ruangguru application is in supporting online learning activities. Therefore, this study aimed to know the process of learning chemistry in the Ruangguru online learning media, especially on the solubility product and solubility product constant (Ksp). The type of research used was descriptive qualitative. Data collection techniques used observation and documentation. The results showed that the Ruangguru application met the criteria in supporting the online learning system of solubility and solubility product constant (Ksp) materials, which had facilities with learning materials delivered via live streaming video with the guidance of online tutors. In addition, there were facilities that could support all student activities, such as the availability of study modules, study groups, and learning evaluations. These are in order to improve students understanding abilities and have a good impact on the learning outcomes obtained, which has facilities with learning materials delivered via live streaming videos with the guidance of online tutors.